The Meaning of the Tulak Bla Dance Ritual of the Siulak Mukai Community in Kerinci Regency - Apdelmi; Wahyuni, Alzadila (SINGOSARI: Jurnal Perkumpulan Prodi Pendidikan Sejarah Se-Indonesia (P3SI) Wilayah Jawa Timur, 2025)
The Tulak Bla Dance ritual is an expression of the animist beliefs of the Siulak Mukai Kerinci community, Jambi Province, which is integrated through sacred dance to ward off disasters or natural disasters, reflecting harmony between humans, nature, and spiritual forces. This study aims to analyze the symbolic meaning of the dance in the ritual, the dynamics of its implementation, and its role in strengthening cultural and social resilience in the modern era. Adopting a qualitative ethnographic approach, data were obtained through participant observation of dance performances, interviews with traditional dancers and community leaders, and analysis of Kerinci cultural archives. The main findings indicate that the Tulak Bla Dance symbolizes the exorcism of evil spirits through rhythmic movements, traditional costumes, and gamelan music accompaniment, accompanied by offerings, aimed at preventing disasters such as drought or disease outbreaks. This ritual not only functions as a religious medium but also as a means of transmitting the values ​​of mutual cooperation and ethnic identity. However, the influence of globalization and urbanization threatens the sustainability of its practice. In conclusion, the Tulak Bla Dance as a form of belief of the Siulak Mukai Kerinci community, offers insights into the integration of dance art in disaster mitigation, with suggestions for development through cultural education and festivals for the preservation of this heritage.